'Children Out of Place' and Human Rights : In Memory of Judith Ennew - Invernizzi, Antonella; Liebel, Manfred; Milne, Brian; Budde, Rebecca (Springer International Publishing : Imprint: Springer, 2017)
This volume brings together tributes to Judith Ennew's work and approach based on issues related to children she once referred to as 'out of place', that is to say children whose living conditions and ways of life appear far removed from Western images of childhood. It includes contributions on working children, children living on the street, orphans and victims of sexual exploitation. It covers developments and concepts used by Judith Ennew with an emphasis on perspectives of children's human rights, their participation, cultural sensitivity, research methodology, methods, ethics, monitoring, policy making and programming. In so doing, it brings together material that form a holistic view of not only her way of thinking, but of a policy and programming agenda developed by a number of researchers, academics and activists since the adoption of the UN Convention on the Rights of the Child.
Keywords: Social sciences.; Child development.; Human rights.; Well-being.; Children.; Cross-cultural psychology.; elektronické knihy; electronic books